DESIGN OF EBB AND FLOW AUTOMATIC HYDROPONIC SYSTEM FOR CHILLI PEPPER CULTIVATION - Delya, Buti (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2015)
Ebb and flowhydroponic systemgenerally used a timer to controlnutrient addition. The use of the timer, however has major disadvantage including inefficiency of nutrient usage. This research aimed at designing of ebb and flow automatic hydroponic system which able to turn on/off the pump based on the moisture content using microcontroller.The research was conducted at Greenhouse Facility of the Integrated Field Lab of Agriculture School, the University of Lampung from April - June 2014. The procedure begins with the manufacture of instrument, calibration, system design tool, the power supply circuit, equipment test and field test. The results showed that has been successfully realized automatic ebb and flow hydroponic system working based on the moisture content. The value of setting point obtained for controling water content for turning on the pump was < 34.95%andturning off the pumpwas > 69.83%. Cultivation testusingchilli pepper resulted thatautomatic ebb and flowhydroponic systemwas significally better thanmanually systemone, interms of plantheight and number of leaves.